Delivery room skin‐to‐skin contact for preterm infants—A randomized clinical trial. (16th September 2019) - Mehler, Katrin; Hucklenbruch‐Rother, Eva; Trautmann‐Villalba, Patricia; Becker, Ingrid; Roth, Bernhard; Kribs, Angela
Abstract: Aim: To investigate the effects of 60 minutes delivery room skin‐to‐skin contact (DR‐SSC) compared with 5 minutes visual contact (VC) on mother‐child interaction (MCI), salivary cortisol, maternal depression, stress and bonding at 6 months corrected age. Methods: A single‐centre randomized controlled trial conducted in a German level III NICU. Eighty‐eight preterm infants (25‐32 weeks of gestational age) were randomized after initial stabilization to either 60 minutes DR‐SSC or 5 minutes VC. Forty‐five infants were allocated to DR‐SSC, 43 to VC. Results: Delivery room skin‐to‐skin contact dyads showed a higher quantity of maternal motoric (18 vs 15, P = .030), infant's vocal (7 vs 5, P = .044) and motoric (20 vs 15, P = .032) responses. Moreover, the combined score of maternal and infant responsive behaviour was higher (86 vs 71, P = .041) in DR‐SSC dyads. DR‐SSC mothers had lower risk of both, early postpartum depression (15% vs 45%, P = .003) and impaired bonding (Score 3 vs 5, P = .031). Conclusion: In addition to regular intermittent kangaroo mother care, DR‐SSC promotes MCI and decreases risk of maternal depression and bonding problems. Thus, DR‐SSC may have positive effects on preterm development.